2020
DOI: 10.21203/rs.3.rs-71086/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico dynamics of COVID-19 phenotypes for optimizing clinical management

Abstract: Understanding the underlying mechanisms of COVID-19 progression and the impact of various pharmaceutical interventions is crucial for the clinical management of the disease. We developed a comprehensive mathematical framework based on the known mechanisms of the SARS-CoV-2 virus infection, incorporating the renin-angiotensin system and ACE2, which the virus exploits for cellular entry, key elements of the innate and adaptive immune responses, the role of inflammatory cytokines and the coagulation cascade for t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…This is being done using multiscale simulation-based models. 78,79,80 These models keep track of the complex molecular interactions involved in viral infection and virus replication within cells as well as spatial spread of the virus, the production of cytokines and chemokines, and the population dynamics of various types of immune cells, such as macrophages, neutrophils, CD4 + T cells, CD8 + T cells, etc. This modeling approach offers a unique opportunity to integrate existing knowledge about viral infection and the induced response of various immune molecules and cells.…”
Section: Adaptive Immune Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is being done using multiscale simulation-based models. 78,79,80 These models keep track of the complex molecular interactions involved in viral infection and virus replication within cells as well as spatial spread of the virus, the production of cytokines and chemokines, and the population dynamics of various types of immune cells, such as macrophages, neutrophils, CD4 + T cells, CD8 + T cells, etc. This modeling approach offers a unique opportunity to integrate existing knowledge about viral infection and the induced response of various immune molecules and cells.…”
Section: Adaptive Immune Modelmentioning
confidence: 99%
“…In contrast to the approaches above, where the models focused only on key aspects of the immune response and their impact on viral dynamics, another approach is to incorporate much more detailed information about the innate and adaptive immune responses as well as comorbidities induced by the virus. This is being done using multiscale simulation‐based models 78,79,80 . These models keep track of the complex molecular interactions involved in viral infection and virus replication within cells as well as spatial spread of the virus, the production of cytokines and chemokines, and the population dynamics of various types of immune cells, such as macrophages, neutrophils, CD4 + T cells, CD8 + T cells, etc.…”
Section: Modeling Sars‐cov‐2 Infection and Treatmentmentioning
confidence: 99%
“…In conclusion, we have quantified the adaptive-immune-response heterogeneity from non-survivors to survivors of COVID-19, using a dynamical motif with 19 measurable parameters beyond the overcomplication of the previous multiscale model 24 . For the first time, this model provides an accurate description of real-time clinical data involving hundreds of patients, which then reliably clarifies T cells' dominant roles in the antiviral and anti-inflammatory immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of previous multiscale simulations [22][23][24] due to considerable parameter value uncertainties stems from the fact that, in the bottom-up strategy, the immune response to infectious disease is modeled as a complex network of numerous factors, resulting in the so-called 'curse of dimensionality' 25 . In contrast, a recent successful model of a classical complex system, namely, fluid turbulence, one of us has demonstrated that the global motions composed of numerous components typically display a symmetry-breaking which can be quantitatively modeled with finite functional variables, called order functions 26,27 .…”
Section: Causal Network Of the Antiviral-inflammation Modelmentioning
confidence: 99%
See 1 more Smart Citation